Integritas Gembala Yang Baik Berdasarkan Yohanes 10:1-21 Bagi Perintisan Gereja - Calvin Revormasi Zai; Stenly Reinal Paparang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
A shepherd must have the same fundamentals as the Lord Jesus, by leading and directing the flock or believers who are always based on high integrity so that the community is always intact. This means that besides believing that the Father (God) is a good shepherd, we are also obliged as His children to have good character. This writing aims to explore the life of a good shepherd in church planting so that from time to time believers remain intact and can increase. The book of John 10:1-21 is the main foundation as well as direction for shepherds to be even better. The integrity of a good shepherd must be able to manifest himself as a servant for all of his sheep. Thus, the community of believers is increasing because of the presence of a servant-hearted shepherd. In this case, keep directing your heart and eyes only to God, not to humans.